Effectiveness of hepatoprotective drugs for anti-tuberculosis drug-induced hepatotoxicity: a retrospective analysis. Issue 1 (December 2016) - Saito, Zenya; Kaneko, Yugo; Kinoshita, Akira; Kurita, Yusuke; Odashima, Kyuto; Horikiri, Tsugumi; Yoshii, Yutaka; Seki, Aya; Seki, Yoshitaka; Takeda, Hiroshi; Kuwano, Kazuyoshi
Abstract Background The effectiveness of hepatoprotective drugs for DIH (drug induced hepatotoxicity) during tuberculosis treatment is not clear. We evaluated the effectiveness of hepatoprotective drugs by comparing the period until the normalization of hepatic enzymes between patients who were prescribed with the hepatoprotective drugs after DIH was occurred and patients who were not prescribed with the hepatoprotective drugs. Methods During 2006–2010, 389 patients with active tuberculosis were included in this study. DIH was defined as elevation of peak serum aspartate aminotransferase (AST) and/or alanine aminotransferase (ALT) of more than twice the upper limit of normal (ULN). We divided the patients into the severe (peak serum AST and/or ALT elevation of >5 times the ULN), moderate (peak serum AST and/or ALT elevation of >3 to ≤5 times the ULN), and mild DIH groups (peak serum AST and/or ALT elevation of >2 to ≤3 times the ULN). We compared the average period until the normalization of hepatic enzymes between patient subgroups with and without hepatoprotective drugs (ursodeoxycholic acid: UDCA, stronger neo-minophagen C: SNMC, and glycyrrhizin). Results In the severe group, there was no significant difference in the average period until the normalization between subgroups with and without hepatoprotective drugs (21.4 ± 10.8 vs 21.5 ± 11.1 days, P  = 0.97). In the mild group, the period was longer in the subgroup with hepatoprotective drugs than that without hepatoprotective drugs (15.7 ± 6.2 vs 12.4 ± 7.9 days, P  = 0.046). Conclusion Regardless of the severity, hepatoprotective drugs did not shorten the period until the normalization of hepatic enzymes.